DESIGN, OPTIMIZATION AND IN VITRO CHARACTERIZATION OF SELF NANO EMULSIFYING DRUG DELIVERY SYSTEM OF OLMESARTAN MEDOXOMIL - Sisinthy, Sreenivas Patro; Rao, Nalamolu Koteswara; Sarah, Chin Yi Lynn (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: The objective of the present study was to design, optimise and characterise self nano emulsifying drug delivery systems (SNEDDS) for a poorly water soluble drug, olmesartan medoxomil (OLM) by Formulation by Design (FbD) approach with an aim to improve its solubility and dissolution. Methods: The SNEDDS were systematically optimised using three factorÂ Box-Behnken design. Concentration of formulation variables, namely, the oil phaseX1 (Capryol 90), the surfactant X2 (Cremophor EL), and the co-surfactant X3 (Transcutol P), was optimized for its impact on mean globule size (Y1), percentage drug release in 20 min (Y2) and turbidity (Y3) of the formulation. Ternary phase diagrams were constructed to select the areas of nanoemulsion and the amounts of oil, surfactant and cosurfactants as critical formulation variables. The prepared SNEDDS were characterised for globule size, dissolution studies, turbidity, and transmission electron microscopy (TEM). Results: Following optimisation, the values of formulation variables were found to be 142.276 mg (Capryol P), 399.999 mg (Cremophor EL) and 598.871 mg (Transcutol P) which produced a globule size of 12.64 nm, percentage drug release of 93.34% and a turbidity of 0.02 FNU. TEM studies demonstrated spherical droplet morphology. Conclusion: Thus, the present studies reveal that the SNEDDS is a promising drug delivery system approach for the enhancement of solubility and dissolution rate of OLM.